Demonstration of an Association between Chlamydia pneumoniae Infection and Venous Thromboembolic Disease - Lozinguez, Olivier; Arnaud, Emmanuel; Belec, Laurent; Nicaud, Viviane; Alhenc-Gelas, Martine; Fiessinger, Jean-Noël; Aiach, Martine; Emmerich, Joseph (Thrombosis and Haemostasis, 2000)
Chlamydia pneumoniae infection has been linked to atherosclerosis, but a possible relationship with venous thromboembolism (VTE) has not been sought. We determined circulating anti-C. pneumoniae antibody levels in patients with VTE. We studied 176 case patients with objectively diagnosed VTE and 197 age-and sex-matched healthy controls, in a retrospective study. Acquired risk factors for VTE and frequent predisposing genetic factors (factor V Arg 506 Gln and factor II G 20210 A mutations) were assessed in all the subjects. Anti-C. pneumoniae IgG antibodies were determined by microimmunofluorescence. All positive plasma samples (titer ≥128) were precisely quantified and tested for the presence of specific IgM antibodies. Fiftyfour percent of the cases and 15.9% of the controls had specific IgG titers of at least 256 (p <0.0001). The crude odds ratio for VTE was 6.2 (95% CI, 3.8-10.1), and rose to 7.7 (4.5-13.2) after excluding subjects carrying the factor V Arg 506 Gln or factor II G 20210 A mutations. The odds ratio for VTE increased with the IgG titer: the adjusted odds ratios were 2.1 (95% CI, 1.1-4.1), 5.3 (2.7-10.6) and 33.0 (4.4-248.4) for titers of 256, 512 and 1024, respectively. Only one subject (a case patient) with a high IgG titer (≥256) also had specific IgM. High titers of anti-C. pneumoniae IgG antibodies are frequently found in patients with previous venous thromboembolism. This association deserves to be confirmed in other case-control studies and prospective studies.All authors have reviewed the manuscript and agree with its content.
Keywords: Deep vein thrombosis; pulmonary embolism; venous thromboembolism; chlamydia pneumoniae; thrombosis